A Biscuit Containing Fucoxanthin Prevents Colorectal Carcinogenesis in Mice. (26th November 2022) - Terasaki, Masaru; Murase, Wataru; Kamakura, Yukino; Kawakami, Serina; Kubota, Atsuhito; Kojima, Hiroyuki; Ohta, Tohru; Tanaka, Takuji; Maeda, Hayato; Miyashita, Kazuo; Mutoh, Michihiro
ABSTRACT: Fucoxanthin (Fx) is a critical pigment required for photosynthesis in brown algae and microalgae. Fx is also a dietary marine carotenoid that with potent anticancer activity in vitro and in vivo. Some popular light meals for increased satiety, such as biscuits, cereals, and crackers, are frequently fortified with micronutrients for human health benefits. However, data on the anticancer potential of Fx-supplemented light meals in humans and animal models remain limited. In the present study, we investigated the anticancer effects of a Fx-supplemented biscuit using a carcinogenic murine azoxymethane/dextran sodium sulfate (AOM/DSS) model. We observed that periodic administration of biscuits containing 0.3% Fx (Fx-biscuit) at an interval of 3 days (each 15 h) per week for 15 weeks significantly inhibited colorectal carcinogenesis in AOM/DSS mice. Comprehensive gene analysis demonstrated that the Fx-biscuit significantly altered the expression of 138 genes in the colorectal mucosal tissue of the mice. In particular, the expression of heat shock protein 70 (HSP70) genes, Hspa1b (–35.7 - fold) and Hspa1a (–34.9 - fold), was markedly downregulated. HSP70 is a polyfunctional chaperone protein that is involved in cancer development. Compared to the control-biscuit group, the number of cells with markedly high fluorescence for HSP70 protein (HSP70 high ) in colorectal mucosal crypts and adenocarcinomas significantly reduced by 0.3- and 0.2-fold, respectively, in the Fx-biscuit group. Our results suggested that Fx-biscuit possesses chemopreventive potential in the colorectal cancer of AOM/DSS mice via the downregulation of HSP70.